Genetic Variation and Phylogenetic Analysis of Indonesian Sugarcane (Saccharum officinarum L.) based on Internal Transcribed Spacer (ITS-nrDNA) - Ganies Riza Aristya; Thoriq Abdul Halim; Tiara Putria Judith; Rina Sri Kasiamdari; Janis Damaiyani; Heri Prabowo (Tropical Life Sciences Research, 2026)
Sugarcane (Saccharum officinarum L.) is a crucial agricultural crop in global sugar production. Over the past decade (2010–2019), sugarcane production in Indonesia has experienced annual fluctuations, reaching its peak in 2013 with 35.5 million tons and declining to 27.7 million tons in 2019. Concurrently, Indonesia’s sugar production only met 38% of domestic demand, necessitating the development of superior sugarcane cultivars with high sucrose content and resistance to pests and diseases. The aim of this study was to identify and determine the relationship among three sugarcane cultivars in Indonesia using DNA barcoding and constructing a phylogenetic tree based on ITS nuclear ribosomal DNA sequences. The ITS region was amplified using the primers ITS1 and ITS4, yielding a final base pair length of 531 bp. The sequences were then analysed to construct a phylogenetic tree using Maximum-Likelihood (ML) and Bayesian Inference (BI) methods. Sequence analysis was also conducted to determine genetic distances, polymorphic sites, haplotype distributions and Principal Coordinate Analysis (PCoA). Phylogenetic tree construction grouped all cultivars into three distinct clades for both methods, with all three cultivars placed in the same clade with a bootstrap value of 94 for ML and a posterior probability of 1 for BI. Haplotype distribution showed that cultivars POJ and Pringu belonged to the same group, and PCoA analysis indicated no separation based on geographic origin, with some compositions similar to those of other countries such as Mexico, Taiwan and China.